PENJATUHAN SANKSI DI BAWAH PIDANA MINIMUM KHUSUS TERHADAP TINDAK PIDANA KORUPSI (STUDI PUTUSAN NOMOR 34 / PID . SUS – TPK / 2021 / PN JKT. PST): Imposing Sanctions Under The Minimum Criminal Specifically For Criminal Acts Of Corruption (Study Decision Number 34 / Pid . Sus – Tpk / 2021 / Pn Jkt .Pst) - Dira Claudia Hasnah Siagian Siregar; Azmi Syahputra (AMICUS CURIAE, 2025)
The law enforcement process for corruption cases is not simple because there are still often differences in the sentencing of crimes. The identification problem in writing this journal is what is the basis for the judge's consideration in imposing sanctions on Decision Number 34 / Pid. Sus – TPK / 2021 / PN JKT . PST is in line with Article 197 paragraph (1) letter f of the Criminal Code and how the legal consequences for the judge are not covered as required by Article 197 paragraph (1) letter f of the Criminal Procedure Code which when adjusted to the indictment is used as the basis for the judge's consideration and is also associated with Article 2 paragraph (1) of the Corruption Crime Law. The type of research used is normative, the nature of the study is descriptive, the data used is secondary data. Qualitative is the analysis of the data used and the method of drawing deductive conclusions. In conclusion, the Judge in deciding this case with a criminal offense that is not by the relevant laws in force even under the special minimum provisions that have been determined in the relevant article listed in the public prosecutor's indictment and is the basis for the judge's consideration.